STRUCTURAL CHARACTERISTICS OF TOURISM SERVICE PROVIDERS IN BIHAR COUNTY, SPATIAL DIMENSIONS OF ENTERPRISES - Czuczor, Krisztina (Acta Carolus Robertus, 2021)
Bihor County has a complex tourism capital, numerous tourism development activities have been implemented recently, although the latest researches do not involve the socio-economic weight of that business sector which enables the overnight stay or consumption by tourists, also the classification of the area as a destination. The aim of the present research is to explore the territorial structure of currently functioning hospitality service providers, therefore I examined them on the basis of their field of activity, sales revenue and the annual average number of employees within the period 2005–2020. Following the literature research, I generated two separate inventories of accommodation providers and hospitality unites for Bihor County according to their activity fields, which contain all still functioning companies until 15th of June, 2021. Subsequently, I classified the territories of local governments of Bihor County into potential destination types based on their characteristics and location, and then examined the distribution of companies according their abovementioned data. According to this research, the time horizon also allows the spatial-economic analysis of the effects of two critical events, the economic crisis and the pandemic. The latter, according to the examined indicators, brought a greater negative impact on the businesses. In conclusion, there are large territorial differences in Bihor County according to the data of the two groups of companies, although distinct trends characterized the local, destination type and county levels which could refer to the successfulness of an area as a tourist destination. I illustrate the results by cartographic methods, in the breakdown of local administrative units.